Pengaruh Pembelajaran Kewirausahaan Dan Entrepreneurial Experience Terhadap Mindset Berwirausaha Generasi Z Melalui Self-efficacy Sebagai Variabel Mediasi - Andi Aulya Zaskia Fitra Mawahda; Tuti Supatminingsih; Andi Tenri Ampa; Andi Annisa Sulolipu; Nurjannah Nurjannah (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to analyze the effect of entrepreneurship education and entrepreneurial experience on Generation Z’s entrepreneurial mindset through Self-efficacy as a mediating variable. The research employs a quantitative approach using Structural Equation Modeling (SEM) as the analytical technique. The results indicate that entrepreneurship education and entrepreneurial experience have a positive and significant effect on Self-efficacy as well as on Generation Z’s entrepreneurial mindset. Furthermore, Self-efficacy is proven to mediate the relationship between entrepreneurship education and entrepreneurial experience and the entrepreneurial mindset. These findings emphasize the importance of strengthening entrepreneurship education and providing real entrepreneurial experiences in shaping the entrepreneurial mindset of Generation Z.